2007
DOI: 10.1007/s10620-007-9960-8
|View full text |Cite
|
Sign up to set email alerts
|

Response of Combination Therapy on Viral Load and Disease Severity in Chronic Hepatitis C

Abstract: Influence of genotypes on viral kinetics and disease severity in chronic hepatitis C (CH-C) patients has been implicated, but requires further investigation. The 41 HCV patients were genotyped by restriction fragment length polymorphism and included for 48 weeks of combination therapy on the basis of clinical (alanine amino transferase > or =60 IU/l) and histological features (histological activity index > or =3). A significant number (30/41) of patients (6/9 of genotype 1, 23/30 of genotype 3 and 1/2 of mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Total RNA was extracted using the TRI® reagent BD (Sigma–Aldrich, St. Louis) from serum samples as per the manufactures instructions. The polymerase chain reaction was performed to detect HCV RNA followed by genotyping using restriction fragment length polymorphism as described previously by our research group . Quantification of HCV RNA was done once in the patients at the time of biopsy who were not on therapy while twice in the patients who were on therapy, once at the initiation of treatment and secondly on completion of treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was extracted using the TRI® reagent BD (Sigma–Aldrich, St. Louis) from serum samples as per the manufactures instructions. The polymerase chain reaction was performed to detect HCV RNA followed by genotyping using restriction fragment length polymorphism as described previously by our research group . Quantification of HCV RNA was done once in the patients at the time of biopsy who were not on therapy while twice in the patients who were on therapy, once at the initiation of treatment and secondly on completion of treatment.…”
Section: Methodsmentioning
confidence: 99%
“…It is supposed that both viral and host factors collectively unable the host immune system to clear the initial viral infection and leads to chronic HCV infection . The patients infected with different HCV genotype have different treatment regime therefore the significant viral factor “HCV genotype” need to be checked while doing the correlation study of the host factors with the outcome of HCV infection …”
Section: Introductionmentioning
confidence: 99%
“…The nested RT-PCR was performed using an Accupower PCR PreMix (Bioneer Corp., Daejeon, South Korea) with the following conditions for both the first and nested rounds of PCR: 94°C for 5 minutes, 35 cycles at 94°C for 30 seconds, 50°C for 40 seconds, and 72°C for 40 seconds, followed by 72°C for 5 minutes. The primers were adopted from the study by Kumar et al (33). Primers used for the first round reaction included the following: HG1, 5’-ATGTACCCCATGAKRTCGGC-3’ and HG2, 5’-ACTGCCTGATAGGGTGCTTGCGAG-3’; the nested round reaction used the following primers: HG3, 5’-CAYGTRAGGGTATCGATGAC-3’ and HG4, 5’-AGGTCTCGTAGACCGTGCATCATG-3’.…”
Section: Methodsmentioning
confidence: 99%
“…Further, subgroup analyses showed that the best outcomes were achieved in studies in which patients were either predominantly HIV-negative (HIV−), predominantly infected with an HCV genotype other than 1 or 4, or treated with ribavirin. The proportion of patients who achieved an SVR in the 20 studies that included patients with all three of these characteristics ranged from 45% (95% CI: 34-55) 70 to 78% (95% CI: 61-91) 71 and the pooled proportion was 65% (95% CI: [61][62][63][64][65][66][67][68]. The presence of the interleukin-28B polymorphism was associated with a high SVR rate in the two studies which reported relevant data.…”
Section: Study Outcomesmentioning
confidence: 99%